The protection of human trafficking victims in Malaysia - Ab Hamid, Zuraini; Mohamad Amin, Noorshuhadawati; Ab Aziz, Norjihan (2018)
United States is a self-appointed country which monitors the issue of human trafficking. In 2001, the U.S Department of State introduced the Trafficking in Persons (TIP) report as an effort to eradicate human trafficking. The country oversees 187 state governments on their progress in addressing human trafficking by collecting relevant information from the United Nations High Commissioner for Refugees, the consulates and embassies around the globe, the United Nations Children’s Fund, and media reports. In the period of 2012 until 2017, the TIP reports highlighted that the Malaysian government did not manage to protect the trafficking victims effectively. As a result, Malaysia is not included among the Tier 1 countries and it has to ensure strict compliance with Section 108 of the Trafficking Victims Protection Reauthorization Act. The protection of victims in Malaysia is entrusted to a number of stakeholders, namely five enforcement bodies led by the Royal Malaysian Police. This paper examined the protection provided to the human trafficking victims by these enforcement bodies. The findings revealed that the enforcement bodies comply with the guidelines and legal framework in Malaysia, despite the claim that they provide inadequate protection. As a recommendation, Malaysia may reflect on the efforts undertaken by the Australian government to protect victims in their country. This approach is anticipated to catapult Malaysia into the Tier 1 ranking in TIP by the year 2020.